ICT curriculum responsiveness and graduate employability. - Mabuela, Innocentia Menge. (My University, 2014)
ABSTRACT The purpose of this study is to investigate and explore curriculum responsiveness and graduate employability in order to establish how two specific ICT programmes offered in one of the merged higher education institutions, ‘Institution XY, responded in preparing graduates to enter the labour market as trained and skilled members of the labour force. This research is a qualitative, interpretive study of two ICT programmes to explore how they respond in trying to be responsive and produce employable graduates from the perspective of graduates, employers and lecturers. The researcher conducted interviews with a purposeful sample of lecturers and employers of students from ‘Institution XY,’ a University of Technology in South Africa. The results indicated that the majority of graduates saw a programming language such as C++ and C# as giving them a solid background about software development, hence they were employed and were able to adapt to any programme language used in the information communication technology (ICT) industry/sector. However, graduates and employers thought that the curriculum lacked soft skills focus such as communication, financial and project management. A few of the lecturers indicated that there was a unit that dealt with employability and did not see it as part of their role. All the lecturers indicated that the curriculum was responsive because most of their graduates were employed. The report concludes and recommends that employability soft skills should be included in the curriculum and that participation of the ICT industry in the advisory board should be broadened in order to align the curriculum to industry demands.
MM 2013
Keywords: Employability,Information technology -- Study and teaching (Higher),Universities and colleges -- Curricula.